Adherence to alcohol consumption-related recommendations and predictors of heavy episodic drinking among patients with NCDs during the COVID-19 pandemic - Muluken Basa; Jan de Vries; David McDonagh; Catherine Comiskey (PLoS ONE, 2025)
Introduction Managing non-communicable diseases (NCDs) requires adherence to lifestyle recommendations like a healthy diet, regular exercise, smoking cessation, and limiting alcohol intake. The COVID-19 pandemic introduced barriers to maintaining these habits, including limited healthcare access, increased stress, and reduced physical activity. This study assessed adherence to lifestyle recommendations, with a focus on heavy episodic drinking (HED), among NCD patients during the pandemic in Arba Minch, Ethiopia, to identify areas for public health intervention. Method A cross-sectional study was conducted among 310 randomly selected NCD follow-up patients at Arba Minch General Hospital. The data was collected using the WHO STEPS and Coronavirus Anxiety Scale (CAS) tool from March 1 to April 30, 2022. Data analysis included both descriptive and inferential statistics (bivariate analyses and multivariable logistic regression). Confounding variables were identified and controlled for to ensure result accuracy. Results Adherence to lifestyle recommendations was found to be low, at just 16.1% [n=50, 95% Confidence Interval (CI) (12.5–20.6%)]. The prevalence of HED was 12.6%, with a higher prevalence among males (18.4%) compared to females (7.4%). Recent alcohol consumption was reported by 29.0% of participants, and among these, 43.3% engaged in HED. Factors significantly associated with HED included male gender (Adjusted Odds Ratio (AOR) 2.63, 95% CI 1.11, 6.24), higher education level (AOR 2.91, 95% CI 1.11, 7.58), and current tobacco use (AOR 6.36, 95% CI 1.62, 25.04). Healthcare disruptions due to COVID-19 (AOR 3.28, 95% CI 1.16, 9.26) and COVID-19-related anxiety (AOR 1.29, 95% CI 1.06, 1.56) were also linked to HED. Conclusion The study revealed low adherence to lifestyle recommendationsand significant prevalence of HED among NCD patients during the pandemic. Associations between HED, healthcare disruptions, and anxiety highlight the critical role of mental health and healthcare access in risky behaviors. Targeted public health interventions are essential, including community-based alcohol reduction programs, improved mental health support, and stronger healthcare systems. Integrating mental health services and culturally sensitive health education and community engagement can help improve adherence to lifestyle recommendations.